2015
DOI: 10.46654/ij.24889849.s6102
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Cost and Financial Performance of Oil and Gas Companies in Nigeria

Abstract: This study ascertained the extent environmental cost affects financial performance of oil and gas companies in Nigeria. The specific objectives were to determine the effect of: community development cost and environmental remediation cost on Tobin’s on oil and gas companies in Nigeria. Ex post facto research design was employed and data was obtained from annual reports and accounts for the periods 2011 to 2018. The hypotheses were tested using regression analysis with aid of e-view 9.0. The results of the empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 10 publications
6
16
1
Order By: Relevance
“…Findings showed that business location costs exert a negative and highly significant effect on financial performance, while research and development costs and social costs have no significant effect on the financial performance of selected sampled extractive industries in Nigeria. The result negates the argument of Ahmed, Muhammed, and Jubril (2017).…”
Section: Fixed Effect Testmentioning
confidence: 60%
See 3 more Smart Citations
“…Findings showed that business location costs exert a negative and highly significant effect on financial performance, while research and development costs and social costs have no significant effect on the financial performance of selected sampled extractive industries in Nigeria. The result negates the argument of Ahmed, Muhammed, and Jubril (2017).…”
Section: Fixed Effect Testmentioning
confidence: 60%
“…Corporate performance is no longer seen simply as a measure of profitability alone rather information on accounting for investment on environmental conservation is equally important. All categories of cost are to be considered as it arises so as to accord it the appropriate treatment in line with the international accounting principle of Generally Accepted Accounting Principle (GAAP) (Nwaiwu and Oluka, 2018). Environmental cost can be defined as the generation and analysis of both financial and non-financial information in order to support internal environmental conservation.…”
Section: Literature Review Environmental Costmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Nwaiwu and Oluka (2018) examine the effect of environmental cost and financial performance measures of quoted oil and gas companies in Nigeria. Time series data were collected from annual financial reporting and economic review of Central Bank of Nigeria.…”
Section: Empirical Reviewmentioning
confidence: 99%